2020
DOI: 10.3390/jcm9020458
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Targets in Diabetic Nephropathy

Abstract: One of the most frequent complications in patients with diabetes mellitus is diabetic nephropathy (DN). At present, it constitutes the first cause of end stage renal disease, and the main cause of cardiovascular morbidity and mortality in these patients. Therefore, it is clear that new strategies are required to delay the development and the progression of this pathology. This new approach should look beyond the control of traditional risk factors such as hyperglycemia and hypertension. Currently, inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
117
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 217 publications
2
117
0
2
Order By: Relevance
“…As shown in the GO enrichment analysis results, the potential targets of shenzhuo formula acting on DN were mainly associated with various biological processes, such as lipopolysaccharide-mediated signaling pathway, inflammatory response, positive regulation of cyclase activity, protein kinase B signaling, positive regulation of MAP kinase activity, response to estradiol, which have a strongly direct correlation with the pathogenesis of DN [28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 95%
“…As shown in the GO enrichment analysis results, the potential targets of shenzhuo formula acting on DN were mainly associated with various biological processes, such as lipopolysaccharide-mediated signaling pathway, inflammatory response, positive regulation of cyclase activity, protein kinase B signaling, positive regulation of MAP kinase activity, response to estradiol, which have a strongly direct correlation with the pathogenesis of DN [28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 95%
“…In order to further explore the pathogenesis of DKD, our research group obtained a KEGG pathway map of miR-4534 through bioinformatics analysis ( Figure 8 ), of which SIRT1/FOXO signaling pathway ( 30 ) is most closely related to DKD. It is well-known that studies on the pathogenesis of DKD are increasingly focused on inflammatory responses ( 31 ), and FOXO is one of the most well-known pathways. Our research group has been working on the pathogenesis of DKD for a long time and has investigated the role of FOXO1 variant in DKD for the first time ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 68 ] Many studies reported that the proinflammatory cytokines such as MCP1, ICAM1 and TGF‐β1 are elevated in diabetic kidneys and can thus contribute to diabetic nephropathy. [ 12,13 ] It translocates from the cytoplasm to the nucleus and induces the expression of MCP1, ICAM1 and TGF‐β1, leading to inflammation, glomerulosclerosis and tubulointerstitial fibrosis. [ 14 ] The present finding showed that treatment with BMFE caused downregulation of VCAM1, TNF‐α, fibronectin mRNA expression, explaining the protective effect of BMFE against DN through decreasing ROS and contributing to an increase in antioxidant activity in addition to and downregulation of gene expressions of VCAM1, TNF‐α and fibronectin that play a critical role in the glomerulosclerosis and tubulointerstitial fibrosis included in DN.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Many studies reported that the proinflammatory cytokines such as monocyte chemoattractant proteins‐1 (MCP‐1), intercellular adhesion molecule‐1 (ICAM‐1) and transforming growth factors‐β‐1 (TGF‐β‐1) are elevated in diabetic kidneys leading to inflammation state, glomerulosclerosis and tubulointerstitial fibrosis. [ 12‐14 ]…”
Section: Introductionmentioning
confidence: 99%